Methane and the Paris Agreement temperature goals. (24th January 2022) - Cain, Michelle; Jenkins, Stuart; Allen, Myles R.; Lynch, John; Frame, David J.; Macey, Adrian H.; Peters, Glen P.
Abstract : Meeting the Paris Agreement temperature goal necessitates limiting methane (CH4 )-induced warming, in addition to achieving net-zero or (net-negative) carbon dioxide (CO2 ) emissions. In our model, for the median 1.5°C scenario between 2020 and 2050, CH4 mitigation lowers temperatures by 0.1°C; CO2 increases it by 0.2°C. CO2 emissions continue increasing global mean temperature until net-zero emissions are reached, with potential for lowering temperatures with net-negative emissions. By contrast, reducing CH4 emissions starts to reverse CH4 -induced warming within a few decades. These differences are hidden when framing climate mitigation using annual 'CO2 -equivalent' emissions, including targets based on aggregated annual emission rates. We show how the different warming responses to CO2 and CH4 emissions can be accurately aggregated to estimate warming by using 'warming-equivalent emissions', which provide a transparent and convenient method to inform policies and measures for mitigation, or demonstrate progress towards a temperature goal. The method presented (GWP*) uses well-established climate science concepts to relate GWP100 to temperature, as a simple proxy for a climate model. The use of warming-equivalent emissions for nationally determined contributions and long-term strategies would enhance the transparency of stocktakes of progress towards a long-term temperature goal, compared to the use of standard equivalence methods. This article is part of a discussion meeting issue 'Rising methane: is warming feeding warming? (part 2)'.